The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1152/ajprenal.00087.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of the potassium channel KCNQ1 in normal mouse kidney

Abstract: Mechanisms of K+ secretion and absorption along the collecting duct are not understood fully. Because KCNQ1 participates in K+ secretion within the inner ear and stomach, distribution of KCNQ1 in mouse kidney was studied using Northern and Western analyses, RT-PCR of isolated tubules, and immunohistochemistry. Northern blots demonstrated KCNQ1 transcripts in whole kidney. RT-PCR showed KCNQ1 mRNA in isolated distal convoluted tubule (DCT), connecting segment (CNT), collecting ducts (CD), and glomeruli. Immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 43 publications
(44 reference statements)
1
27
0
Order By: Relevance
“…C3H mice were obtained from The Jackson Laboratory (Bar Harbor, ME). Tissues from Black Swiss 129 mice were prepared for a previous study using the same methods described below (46). All animal use protocols were approved by the Institutional Animal Care and Use Committee and in accordance with the animal use guidelines of the American Physiological Society.…”
Section: Methodsmentioning
confidence: 99%
“…C3H mice were obtained from The Jackson Laboratory (Bar Harbor, ME). Tissues from Black Swiss 129 mice were prepared for a previous study using the same methods described below (46). All animal use protocols were approved by the Institutional Animal Care and Use Committee and in accordance with the animal use guidelines of the American Physiological Society.…”
Section: Methodsmentioning
confidence: 99%
“…Immunolocalization of Rhbg and Rhcg was accomplished using immunoperoxidase procedures and a commercially available kit (Mach2, Biocare Medical, Concord, CA) using techniques described in detail previously (33,44,51,55,59). Anti-Rhbg and anti-Rhcg antibodies were used at 1:2,000 and 1:30,000 dilution, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In the mouse kidney, KCNQ1 mRNA is expressed in the PT, DCT, CNT, CD, and glomeruli (Wang, 2004;Zheng et al, 2006). It is also distributed intensely and basolaterally in the DCT and CNT cells (Wang, 2004;Zheng et al, 2006), serving as part of the basolateral potassium channels (Hamilton and Devor, 2012). Recent research results have confirmed that KCNQ1-related potassium channels, which are highly expressed at the apical membrane of proximal convoluted tubule, underlie the K + reabsorption (Wang, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…(Schroeder et al, 2000;Vallon et al, 2001Vallon et al, , 2005Warth et al, 2002;Lang et al, 2007;Yang et al, 2007;Das et al, 2009;Pan et al, 2010;Amin et al, 2012;Sung et al, 2014). In the mouse kidney, KCNQ1 mRNA is expressed in the PT, DCT, CNT, CD, and glomeruli (Wang, 2004;Zheng et al, 2006). It is also distributed intensely and basolaterally in the DCT and CNT cells (Wang, 2004;Zheng et al, 2006), serving as part of the basolateral potassium channels (Hamilton and Devor, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation